Going digital in agriculture: how radio and SMS can scale-up smallholder participation in legume-based sustainable agricultural intensification practices and technologies in Tanzania - Silvia, S.; Musebe, R.; Baars, E.; Ganatra, D.; Romney, Dannie L. (Informa UK Limited, 2021)
In 2016, a study was conducted in Tanzania to assess the impact of radio and SMS in scaling-up smallholder participation in legume-based sustainable agricultural intensification (SAI) practices and technologies. The study aimed to answer the following research questions: (i) does participation in the campaign enhance farmers’ knowledge of legume-based sustainable agricultural intensification practices and technologies? (ii) what is the impact of the campaign on the adoption of legume-based sustainable agricultural intensification practices and technologies?; (iii) does exposure to multiple ICT-enabled channels result in larger gains (in terms of knowledge and adoption) than exposure to only one channel? (iv) is it more cost-effective to use radio or SMS alone or use them in combination? The results show that both awareness and adoption are boosted if SMS supports radio campaigns. However, radio alone is the most cost-effective approach. Each dollar spent on the radio campaign results in 2.1 farmers that have adopted at least one new practice, compared with 0.5 farmers for SMS and 0.4 farmers for radio and SMS combined. Other factors were also important in facilitating uptake of legume-based SAI practices, such as gender, age, education and land size, but were not statistically significant when rated against the communication channels used.